Femoral Pseudoaneurysm in IV Drug Abusers: Single-center Study Experience - Shrestha, Kajan Raj; Gurung, Dinesh; Khanal, Nischal; Shrestha, Uttam Krishna (Journal of Nepal Health Research Council, 2020)
Background: Pseudoaneurysm of the femoral artery is the most common complication among IV drug abusers who inject drugs in groin. These are usually infective and potentially fatal so it requires astute clinical recognition and prompt treatment, possessing a significant challenge to vascular surgeons.Methods: We present a retrospective descriptive study and the prevalent practice of their management covering the period from 2013 July- December 2019 at our center. Data regarding demography, presentation, surgical management, and the outcome was analyzed.Results: Among 368 femoral pseudoaneurysm operated during the period, groin swelling with pulsatile mass was the most frequent presentation accounting 304 (82.61%) patients. About 67.12% (247 patients) of the pseudoaneurysm has purulent discharge and 60.07% (221 patients) had bleeding at presentation out of which 211patients had hepatitis C (HCV), hepatitis B (HBsAg) and/or Human Immunodeficiency virus (HIV) status positive.  Thirty six patients (9.78%) presented with femoral pseudoaneurysm in both groins. Ligation and excision of the pseudoaneurysm were done in all cases while delayed revascularization was done in eight patients with expanded Polytetrafluoroethylene (ePTFE) graft in one patient and venous bypass grafts in other 7 cases. All patients after bypass had no major limb loss and two patients had a patent graft at five years follow up. There were nine mortalities and thirty two patients underwent amputation. Conclusions: Infected femoral pseudoaneurysm can be managed by ligation of the involved artery with delayed revascularization if required without major limb and life loss.Keywords: Delayed revascularization; drug abuser; infected pseudoaneurysm; ligation